PELAKSANAAN POLIGAMI YANG TIDAK SESUAI DENGAN UNDANG-UNDANG NO 1 TAHUN 1974 JO UNDANG-UNDANG NO 16 TAHUN 2019 TENTANG PERKAWINAN (Studi Kasus: Putusan Nomor 311/Pdt.G/2019/PA.Bn) - Nabila Fajarlina Dinda; Hanafi Tanawijawa (Jurnal Hukum Adigama, 2022)
polygamous marriage where a married man then remarries and has more than one wife, basically polygamy in Indonesia is only possible if the person concerned gives permission to do polygamy An application for a polygamy permit must go through the permission of the first wife and a certain institution is required for consideration, the authorized institution is a judge or court, after deliberating and fulfilling all the requirements in court, I conclude whether or not the applicant will give permission to practice polygamy, the court will give permission if the marriage has not reached the goal of marriage. Polygamous marriage cannot be used as a venue for measuring a person's Islam, in which case the more active the polygamist is considered the better his religious position, or the more patient a wife accepts polygamy, the more quality her faith will be or by considering polygamy as sunnah. There have been many men who have married more than once or are called polygamous, in this case the Bengkulu Religious Court Judge granted the application for permission to practice polygamy on condition that it strengthens the alternative and cumulative. If one of these conditions can be proven, then the court can give permission to practice polygamy and the court can grant it if these conditions have been met. And the Court also has to prove whether the wife really cannot carry out her obligations as a wife, has an incurable illness or disability, cannot give birth to offspring.